Representation of identity as cultural citizenship practice: positioning Deepa Mehta, Mira Nair, and Gurinder Chadha in the context of postcolonial theory - Modgill, Arti (2016)
Recent research on cultural citizenship focuses on issues of identity and belonging in multicultural societies and examines the political, economic, and cultural aspects of community membership in local, national, and transnational groups. Postcolonial research into colonial and neocolonial representations of individual and national cultural identities offers a means of interrogating hegemonic discursive practices of Orientalism, neocolonialism and globalization as they relate to the representation of cultural citizenship.